Estructuraciones para analizar realidades complejas - Ramírez Miranda, Ridberth M. (2009)
Knowledge of conceptual architectures makes us look critically at what happens in reality, to adopt a scientific position and use it in a adequate methodology in searching, so, any of them can lead to limits on the arbitrariness of the investigation, to visualize the structure of problems or to promote ideas, both corrective and creative, the goal is to describe a paradigm of the complex, relatively little known, in the field of possible ideas, as well as an overall assessment of complexity and chaos. Globalization comes to the universities, persuading them in making a greater effort to understand and develop useful and relevant knowledge to the production processes. Therefore, it is an unfailing social partnership between universities, businesses and the state to incorporate knowledge, innovation and design and implement coherent strategies to compete in domestic and global markets. The initiative must be primarily scientific teams up with representatives from universities, corporations and the State, to propose strategies that contribute to the development of science and technology in the country.